Abstracts Presented at the Conquering Heart Disease in the Himalayan Region International Conference 2-3 November 2012 - Editor, The (Nepalese Heart Journal, 2013)
DOI: http://dx.doi.org/10.3126/njh.v9i1.8353 Nepalese Heart Journal Vol.9(1) 2012 pp.65-76